Large herbivore assemblages in a changing climate: incorporating water dependence and thermoregulation. (22nd July 2019) - Veldhuis, M. P.; Kihwele, E. S.; Cromsigt, J. P. G. M.; Ogutu, J. O.; Hopcraft, J. G. C.; Owen‐Smith, N.; Olff, H.
Abstract: The coexistence of different species of large herbivores (ungulates) in grasslands and savannas has fascinated ecologists for decades. However, changes in climate, land‐use and trophic structure of ecosystems increasingly jeopardise the persistence of such diverse assemblages. Body size has been used successfully to explain ungulate niche differentiation with regard to food requirements and predation sensitivity. But this single trait axis insufficiently captures interspecific differences in water requirements and thermoregulatory capacity and thus sensitivity to climate change. Here, we develop a two‐dimensional trait space of body size and minimum dung moisture content that characterises the combined food and water requirements of large herbivores. From this, we predict that increased spatial homogeneity in water availability in drylands reduces the number of ungulate species that will coexist. But we also predict that extreme droughts will cause the larger, water‐dependent grazers as wildebeest, zebra and buffalo–dominant species in savanna ecosystems – to be replaced by smaller, less water‐dependent species. Subsequently, we explore how other constraints such as predation risk and thermoregulation are connected to this two‐dimensional framework. Our novel framework integrates multiple simultaneous stressors for herbivores and yields an extensive set of testable hypotheses about the expected changes in large herbivore community composition following climate change.